2005
DOI: 10.1177/1082013205051271
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Method for Producing a Nutritive Protein Extract Powder from Shrimp-head Waste

Abstract: Enzymatic hydrolysis has been widely applied for production of protein hydrolysate from shrimp waste and for purification of chitin. In the present study, shrimp (P. semisulcatus) head waste was hydrolysed, using a commercial proteolytic enzyme, Alcalase. In order to improve protein extraction efficiency, certain chemicals such as sodium sulphite and Triton x-100 were used along with the enzyme. When Alcalase (12 AU/kg) used alone, the yield of protein extraction was 45.1% and by using Triton x-100 (0.01 g/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 14 publications
2
47
0
2
Order By: Relevance
“…Other researchers have reported moisture content of 73-81%, crude protein content of 40-74% (db), lipid content of 0-18% (db) and ash content of 17-30% (db) (Coward-Kelly et al, 2006;Gildberg & Stenberg, 2001;Mizani et al, 2005;Synowiecki & Al-Khateeb, 2000). The composition of the byproducts is dependent on the method used for shrimp processing; for example, compared to the hand-peeling used for shrimp processing in this study, peeling by machinery has a tendency to leave some shrimp meats, often giving higher protein content in the discarded material.…”
Section: Proximate Composition Of Shrimp Processing Byproductsmentioning
confidence: 94%
See 1 more Smart Citation
“…Other researchers have reported moisture content of 73-81%, crude protein content of 40-74% (db), lipid content of 0-18% (db) and ash content of 17-30% (db) (Coward-Kelly et al, 2006;Gildberg & Stenberg, 2001;Mizani et al, 2005;Synowiecki & Al-Khateeb, 2000). The composition of the byproducts is dependent on the method used for shrimp processing; for example, compared to the hand-peeling used for shrimp processing in this study, peeling by machinery has a tendency to leave some shrimp meats, often giving higher protein content in the discarded material.…”
Section: Proximate Composition Of Shrimp Processing Byproductsmentioning
confidence: 94%
“…Investigations have therefore been conducted into generating value-added products from these shrimp processing discards, including the extraction of chitin (Gildberg & Stenberg, 2001;Synowiecki & Al-Khateeb, 2000) and production of protein hydrolysates for use in food and animal feed (Coward-Kelly, Agbogbo, & Holtzapple, 2006;Gildberg & Stenberg, 2001;Mizani, Aminlari, & Khodabandeh, 2005). The potential for producing functional food ingredients through hydrolysis of shrimp byproducts and discards has also been suggested by recent research reports of the angiotensin-I-converting enzyme (ACE) inhibitory activity and antioxidant activity in the oligopeptide-enriched hydrolysates from Acetes chinensis, an underutilised shrimp species (He, Chen, Sun, Zhang, & Gao, 2006), and free radical scavenging activity in hydrolysates from shrimp processing discards (Guerard, Sumaya-Martinez, Laroque, Chabeaud, & Dufosse, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 showed that protein recoveries for all the enzymes increased with time of hydrolysis but the rate of increase get slower at the later stage. Various authors reported that, when compared to other proteolytic enzymes, Alcalase resulted in higher protein recovery, which was again proved for the Paeneus monodon processing waste (Beak and Cadwallader 1995;Shahidi et al 1995, Mizani et al 2005. The decrease in protein recovery in the later stage of hydrolysis can be explained by the slower rate of cleavage of peptide bonds with the elapse of time.…”
Section: Amino Acid Compositionmentioning
confidence: 95%
“…With increasing competition on world markets there is a need to develop value-added products from the waste material to help maintain the economic viability of the industry as well as reduce environmental pollution (Gildberg and Stenberg 2001) Shrimp head and shell generally contain good percentage of protein with balanced amino acid profile and minerals like Ca, P, Na and Zn (Ibrahim et al 1999). Recovery of protein fraction from the shrimp waste by enzymatic hydrolysis has been widely studied (Synowiecki and Alkhateeb 2000;Mizani et al 2005) which has advantages since accelerated hydrolysis allows for control of hydrolysis and thus minimizes undesirable reactions. Protein digesting enzymes breakdown protein in smaller peptide, making hydrolysates most available amino acid source for protein biosynthesis (Gildberg and Stenberg 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have therefore been conducted into generating value-added products from these SPB, including extraction of chitin (Gildberg and Stenberg 2001;Synowiecki and Al-Khatee 2000), production of protein hydrolysates for use in food and animal feed (Coward-Kelly et al 2006;Gildberg and Stenberg 2001;Mizani et al 2005), and extraction of carotenoids Sachindra et al 2006Sachindra et al , 2007Babu et al 2008). …”
Section: Introductionmentioning
confidence: 99%